Analysis of Student Perceptions in the Islamic History and Culture Study Program at Sunan Kalijaga State Islamic University Yogyakarta on the Use of Quizizz as a Medium for Arabic Language Learning Evaluation - Siti Alfi Aliyah; Primasti Nur Yusrin Hidayanti; Muhajir; Imam Muhsin; Ike Fitriana Saraswati (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
This study aims to analyze the perceptions of students in the Islamic History and Culture Study Program at Sunan Kalijaga State Islamic University Yogyakarta regarding the use of Quizizz as an evaluation medium in Arabic language learning. The study focuses on three main aspects: students’ satisfaction, motivation, and knowledge. A qualitative approach with descriptive analysis was employed. Data were collected through observation, documentation, and an online questionnaire distributed via Google Forms. The research population consisted of 31 second-semester students enrolled in the Arabic Language course. The questionnaire instrument was measured using a four-point Likert scale (strongly disagree, disagree, agree, strongly agree) to obtain quantifiable data. The results indicate that the majority of students responded positively to the use of Quizizz as an evaluation tool. This positive response was influenced by the ease of use, appealing interface design, transparency in displaying scores, and the platform’s ability to help students recall and understand the learning material. In addition, the use of Quizizz created a more interactive and enjoyable learning atmosphere, encouraging students to learn more actively and strive for better scores. These findings confirm that integrating interactive digital media such as Quizizz can serve as an effective and innovative evaluation strategy, while also opening opportunities for the development of technology-based learning methods in Arabic language courses.